Multiplex PCR-based next generation sequencing as a novel, targeted and accurate molecular approach for periprosthetic joint infection diagnosis - Huang, Changyu; Huang, Ying; Wang, Ziwen; Lin, Yiming; Li, Yongbin; Chen, Yang; Chen, Xiaoqing; Zhang, Chaofan; Li, Wenbo; Zhang, Wenming; Fang, Xinyu; Huang, Zida (Frontiers in Microbiology, 2023)
Objectives Periprosthetic joint infection (PJI) diagnosis remains challenging, and the identification of the causative microorganism is, by far, the most important aspect. Here, we use multiple PCR-based targeted next-generation sequencing (tNGS) to detect pathogens in PJI. To explore 1. the ability of targeted next-generation sequencing (tNGS) to detect pathogens in PJI; 2. the consistency of tNGS, metagenomic NGS (mNGS), and culture results; and 3. the ability of tNGS to detect drug resistance genes in PJI. Methods PJI was diagnosed according to the Musculoskeletal Infection Society (MSIS) criteria. The microorganisms were detected by culture, mNGS and tNGS to compare the diagnostic effectiveness of the three methods for PJI and to compare their consistency in detecting microorganisms. Drug resistance genes were detected using tNGS. The costs and turnaround times of mNGS and tNGS were compared. Results Forty-three patients with PJI, 21 patients without PJI and 10 negative control cases were included. The culture, tNGS, and mNGS sensitivities for PJI diagnosis were 74.41%, 88.37%, and 93.02%, respectively, with no significant differences. The specificities were 90.48%, 95.24%, and 95.24%, respectively, with no significant differences. tNGS detected drug resistance genes in 37.5% of culture-positive PJIs. tNGS was superior to mNGS for turnaround time (14.5 h vs. 28 h) and cost ($150 vs. $260). Conclusions tNGS can effectively identify PJI pathogens and may provide drug resistance information, while tNGS is superior to mNGS regarding cost and turnaround time. A multidisciplinary, multi-technology based algorithm to diagnose PJI is appropriate. Highlights 298 microorganisms and 86 drug resistance genes were included in the tNGS panel. Diagnostic efficacy of tNGS is not inferior to that of commonly used indicators. tNGS is superior to mNGS in cost and turnaround time.